Andando e parando pelos trechos : uma etnografia das trajetórias de rua em São Carlos - Martinez, Mariana Medina (2011)
The research at hand accounts for São Carlos street paths. In an attempt to avoid defining them, as it is often the case with public policies and even a large part of academical studies, through denominations that they would not be able to relate to, such as homeless people, I have elected the analytical and methodological resource to deal with the street paths through which these dwellers roam. This choice has allowed me to account for the paths segmentations, compositions and transformations that configure the tactics of preservation of life developed by the people who walk these paths, as well as possible courses wandered by the homeless. Among the differences presented in these paths, I describe the bodily changes that come up with these variations, partially constituting a homeless body that is inscribed with the courses in which these subjects roam. In order to talk about the ways of life in the streets, it is necessary to put into perspective a group of urban agents, discourses and apparatuses that legitimate these lives in the street to the eyes of the State and to public policies. I describe this phenomenon through two aspects that allow me to trace some parameters in order to compare life in the streets to that same life as assisted by the social services concerned with the homeless. The ethnography performed in the streets details the ways of appropriation and usage of public spaces, as well as the motions and fluxes that emerge in this context. On the other hand, I account for political (and institutional) management of this population in the city. The ethnography for these institutional spaces was performed in CREAS (Centro de Referência Especializado de Assistência Social [Referral Center Specialized in Social Service], which is directly concerned with the homeless. I constrast two different perspectives on the same phenomenon, since the tension which is evidently exposed allows us to see not only the street paths but its mechanisms of institutionalization, both the paths developed in the street and in the institutions, and even the institutional interventions to which the homeless are submitted to.